1963
DOI: 10.1177/00220345630420017201
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Lesions in Hypercitricemia: Effect of Adrenal Cortical Hormones on the Blood Citric Acid Level and the Periodontal Tissues

Abstract: It is an interesting fact that the citric acid content in blood has apparently increased in patients with advanced alveolar atrophy.1 Insofar as this hypercitricemia appears to be associated with some types of periodontal disease, it was thought to be of interest to investigate the effect of the many factors that influence the citric acid.Numerous workers have studied the effect of fluoroacetate2, 3 vitamin D,4 5 and parathyroid hormone6 on the citric acid and enzyme systems that may be concerned in the format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1964
1964
1990
1990

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Citric acid is not only an important intermediate in energy metabolism but is also closely associated with bone formation and destruction.2 It is well known that fluoroacetate,3' 4vitamin D,5, 6 parathyroid,7' 8and adrenal-cortical hormone9' 10 have a profound effect on the citric-acid metabolism. Banerjee, Biswas, and Singh" have demonstrated that scorbutic animals exhibited an increased amount of blood citric acid and that citric acid accumulated significantly in the body tissues of such animals.…”
mentioning
confidence: 99%
“…Citric acid is not only an important intermediate in energy metabolism but is also closely associated with bone formation and destruction.2 It is well known that fluoroacetate,3' 4vitamin D,5, 6 parathyroid,7' 8and adrenal-cortical hormone9' 10 have a profound effect on the citric-acid metabolism. Banerjee, Biswas, and Singh" have demonstrated that scorbutic animals exhibited an increased amount of blood citric acid and that citric acid accumulated significantly in the body tissues of such animals.…”
mentioning
confidence: 99%